(untitled) (Quinto Sol, 2017)
On September 16th, 1955, a coup led by the Armed Forces brought down the Government of Juan Domingo Perón. That day and the following ones, several uprisings took place simultaneously in different regions of Argentina. This was the corollary of several years of intensification of the conflicts between the heterogeneous antiperonist opposition and the Government. This article explores that process in the province of Corrientes, which was the scene of one of the uprisings. In this context, we discuss the various practices of political control implemented by the Peronist Government and the forms and strategies of opposition, inside and outside the institutional frame, of the different parties acting in the province at that time. In addition, the role of the Catholic Church is examined. This institution had an enormous influence on the society of Corrientes, as it will become a key partner in the success of the coup plans, because of its confrontation with the Government and finally, this work evaluates the participation of the Armed Forces, in particular the organization of the failed revolt in Curuzú Cuatiá.